The Implementation of PhET Simulation Media to Improve The Understanding of Physics Concepts - Irmayani NS; Usman Usman; Ahmad Dahlan; Trisno Setiawan (Universitas Lambung Mangkurat, 2025)
Physics material is often considered a difficult subject because it is abstract, while the limitations of laboratory facilities are also an obstacle in the learning process. In addition, conventional learning media that are still predominantly used make students less motivated and less likely to explore concepts independently. This research aims to determine the improvement in students' conceptual understanding of physics after the implementation of PhET simulation media on the topic of sound waves. The research employed a quantitative approach with a pre-experimental design, specifically a one-group pretest-posttest design. The research subjects were 30 students from class XI-2 of SMAN 20 Gowa. The instrument used was an essay test administered before and after the treatment to measure the level of students’ conceptual understanding. The data were analyzed descriptively to observe the changes in pretest and posttest scores, and the N-Gain formula was used to evaluate the effectiveness of the learning process. The results showed an increase in the average score from 6.9 (pretest) to 20.17 (posttest). The average N Gain score was 0.74, which falls into the high category. These findings indicate that the use of PhET simulation media contributes positively to improving students’ conceptual understanding in physics. Therefore, it can be considered an effective and interactive learning alternative, particularly for abstract topics such as sound waves. The implications of this research confirm that the use of PhET simulation media is not only effective in improving students' understanding of physics concepts but can also be integrated more widely as an alternative learning strategy to overcome the limitations of practicum facilities in schools.